Hypertension-evoked RhoA activity in vascular smooth muscle cells requires RGS5 - Arnold, Caroline; Demirel, Eda; Feldner, Anja; Genové, Guillem; Zhang, Hangjun; Sticht, Carsten; Wieland, Thomas; Hecker, Markus; Heximer, Scott; Korff, Thomas (The FASEB journal, 2018)
G protein-mediated signaling plays a decisive role in blood pressure regulation and the phenotype of vascular smooth muscle cells (VSMCs); however, the relevance of proteins that restrict G protein activity is not well characterized in this context. Here, we investigated the influence of regulator of G protein signaling 5 (RGS5), an inhibitor of Gαq/11 and Gαi/o activity, on blood pressure and the VSMC phenotype during experimental hypertension. In mice, loss of RGS5 did not affect baseline blood pressure, but prevented hypertension-induced structural remodeling. RGS5-deficient arterial VSMCs did not acquire a synthetic phenotype as evidenced by their inability to decrease the abundance of contractile markers—α-smooth muscle actin and smooth muscle-myosin heavy chain—or to proliferate under these conditions. Mechanistically, hypertensive pressure levels or biomechanical stretch are sufficient to increase the expression of RGS5. Loss of RGS5 severely impairs the activation of RhoA and stress fiber formation. In stretch-exposed VSMCs, RhoA activity was amplified upon inhibition of PKC, which mimics the downstream effects evoked by RGS5-mediated inhibition of Gαq/11 signaling. Collectively, our findings underline that RhoA activation may depend on the restriction of G protein activity and identify RGS5 as a mechanosensitive regulatory protein that is required to promote the synthetic VSMC phenotype as a prerequisite for structural renovation of the arterial wall during hypertension.— Arnold, C., Demirel, E., Feldner, A., Genove, G., Zhang, H., Sticht, C., Wieland, T., Hecker, M., Heximer, S., Korff, T. Hypertension-evoked RhoA activity in vascular smooth muscle cells requires RGS5. FASEB J. 32, 2021-2035 (2018). www.fasebj.org